Molecular Characterization of Carbonic Anhydrase II (CA II) and Its Potential Involvement in Regulating Shell Formation in the Pacific Abalone, Haliotis discus hannai - Sharker, Md. Rajib; Sukhan, Zahid Parvez; Sumi, Kanij Rukshana; Choi, Sang Ki; Choi, Kap Seong; Kho, Kang Hee (Frontiers in Molecular Biosciences, 2021)
Carbonic anhydrases (CAs) are a family of metalloenzyme that can catalyze reversible interconversion of CO2/HCO3−, ubiquitously present in both prokaryotes and eukaryotes. In the present study, a CA II (designated as HdhCA II) was sequenced and characterized from the mantle tissue of the Pacific abalone. The complete sequence of HdhCA II was 1169-bp, encoding a polypeptide of 349 amino acids with a NH2 terminal signal peptide and a CA architectural domain. The predicted protein shared 98.57% and 68.59% sequence identities with CA II of H. gigantea and H. tuberculata, respectively. Two putative N-linked glycosylation motifs, and two cysteine residues could potentially form intramolecular disulfide bond were present in HdhCA II. Phylogenetic analysis indicated that HdhCA II was placed in gastropod clade and robustly clustered with CA II of H. gigantea and H. tuberculata. Highest level of HdhCA II mRNA expression was detected in the shell forming mantle tissue. During ontogenesis, the mRNA of HdhCA II was detected in all stages, with larval shell formation stage showing the highest expression level. In situ hybridization results detected the HdhCA II mRNA expression in epithelial cells of the dorsal mantle pallial, an area known to express genes involved in the nacreous layer formation of shell. This is the first report of HdhCA II in the Pacific abalone, and the results of our study indicate that this gene might play a role in shell formation of abalone.